The Dance Lessons in Batik SMPLB B Manunggal District Tegal Slawi - Wardani, Anestia Widya; Triyanto, Triyanto; Hartono, Hartono (Catharsis, 2019)
School (SLB) Manunggal Slawi is one special school run by the foundation "Family Welfare Manunggal", located in Slawi Tegal providing education for children with disabilities one of them deaf (part B). one of the subjects taught is the art of dance with Dance Batik material. The purpose of this study is to analyze the learning process and the results of Batik dance SMPLB B Manunggal Slawi Tegal. This study used qualitative research methods. The collection of data through observation, interviews and documentation. The validity of the data using triangulation. Analysis of data using reduction, presentation and verification of data. The results showed that learning dance SMPLB Batik Manunggal Slawi Tegal B consists of preliminary activities, core activities and closing activity. Batik dance learning outcomes SMPLB B Manunggal Slawi Tegal learners master the competencies dance consisting of wiraga aspect, wirasa, wirama. Wiraga aspect views of learners are able to co-ordinate movement, form and demonstrate simple movements that are part of an appreciation and creative learners. Wirama visible aspect of learners' ability to coordinate movement of the body and mind to knock the appropriate use of hearing aids (hearing aids). Wirasa aspect views of learners have had the courage and have the confidence to demonstrate the ability of the students to express their dancing ability.